Mechanical power remote transmission - Flores, António Manuel Luzano de Quadros (Neutro à Terra, 2021)
Remote transmission of mechanical energy would certainly be a dream two centuries ago. Nowadays we live with it and we may not even realize that we use mechanical energy wherever we want, but that it was actually produced hundreds, if not thousands of miles away. The transmission of mechanical energy from places where it is available to places where it is necessary, is nowadays achieved by means of machines that transform mechanical energy into electrical and electrical into mechanical energy. Electromagnetism plays a fundamental role in the conversion of energy and their understanding is important to have a complete mastery of the subject. The magnetic field that involves the operation of the electric machines can be originated in permanente magnets or can be created by coils. The approach to magnetism created by permanent magnets or coils is usually based on the observable effects and not on the atomic model explanation of these phenomena, using arguments associated with experimental observations, such as "equal poles repel" or "lines of magnetism are closed", without actually giving a physical interpretation. The purpose of this article is to explain the atomic processes associated with the remote transmission of mechanical energy related to magnetic and electrical phenomena, making clear and more transparent concepts such as magnetic poles, attraction / magnetic repulsion interaction, magnetic field, flow, induction, etc.